The first BILGENSA Research Network workshop in Zambia: identifying research priorities, challenges and needs in genital bilharzia in Southern Africa [version 2; peer review: 1 approved, 3 approved with reservations] - Oliva Rabozakandria; Russel Stothard; Tendai Munthali; Anouk Gouvras; Paul Kanfwa; Grace Hameja; Helen Ayles; Halwindi Hikabasa; Kwame Shanaube; Rhoda Ndubani; Anna Kildemoes; Olimpia Lamberti; et al. (Wellcome Open Research)
Female genital schistosomiasis (FGS) and male genital schistosomiasis (MGS) are gender-specific manifestations of urogenital schistosomiasis. Morbidity is a consequence of prolonged inflammation in the human genital tract caused by the entrapped eggs of the waterborne parasite, Schistosoma (S.) haematobium. Both diseases affect the sexual and reproductive health (SRH) of millions of people globally, especially in sub-Sahara Africa (SSA). Awareness and knowledge of these diseases is largely absent among affected communities and healthcare workers in endemic countries. Accurate burden of FGS and MGS disease estimates, single and combined, are absent, mostly due to lack of awareness of both diseases and absence of standardized methods for individual or population-based screening and diagnosis. In addition, there are disparities in country-specific FGS and MGS knowledge, research and implementation approaches, and diagnosis and treatment. There are currently no WHO guidelines to inform practice. The BILGENSA (Genital Bilharzia in Southern Africa) Research Network aimed to create a collaborative multidisciplinary network to advance clinical research of FGS and MGS across Southern African endemic countries. The workshop was held in Lusaka, Zambia over two days in November 2022. Over 150 researchers and stakeholders from different schistosomiasis endemic settings attended. Attendees identified challenges and research priorities around FGS and MGS from their respective countries. Key research themes identified across settings included: 1) To increase the knowledge about the local burden of FGS and MGS; 2) To raise awareness among local communities and healthcare workers; 3) To develop effective and scalable guidelines for disease diagnosis and management; 4) To understand the effect of treatment interventions on disease progression, and 5) To integrate FGS and MGS within other existing sexual and reproductive health (SRH) services. In its first meeting, the BILGENSA Network set forth a common research agenda across S. haematobium endemic countries for the control of FGS and MGS.